GAMBARAN KEMAMPUAN BAHASA PADA ANAK USIA 1-2 TAHUN DI DESA SURU KECAMATAN DAWAR BLANDONG KABUPATEN MOJOKERTO - Khalimatus Sa’diya, Lida (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Children language is the important aspect which need to be developed. Because it is a communication tool with the other. Design of this research is descriptive. The population of this research is all of children who are aged 1-2 years old in Suru District Dawar Blandong Mojokerto. In this research, a part of population was became sample, whereas the sampling used non probability sampling with purposive sampling. Variable of this research was language skill of children who were aged 1-2 years old. The collecting data were processed by editing, coding, scoring, and tabulating. Analyzing data used distribution table. The result of this study was 26 respondents. 17 respondents (65.40%) were the development language skill of age, 6 respondents (23,07%) were the development language skill doubting, and 3 respondents (11,53%) were deviate. From the result of this research was gotten 26 respondents and 9 respondents were not accordance with their aging. So, their parents should train their children to speak and improve to be the best quality of communication.Keywords: language skills, 1-2 years of age